Assessing the Implementation Fidelity of Early Interventions: Data Collection Methods. (December 2020) - Lemire, Colombe; Dionne, Carmen; Rousseau, Michel
Highlights: Several dimensions of implementation fidelity must be assessed. The strengths of one method should counterbalance the weaknesses of another. Evolving nature of implementation: multiple collection time points are needed. A self-reported checklist can serve as a guide to participants to improve fidelity.